Pengaruh Hambatan Samping Terhadap Kinerja Ruas Jalan (Studi Kasus: Jl. Orang Kayo Pingai Kota Jambi) - Ahmad Fadhila Rosyidin (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
This study aims to analyze the effect of side friction activities on the performance of Jalan Orang Kayo Pingai in Jambi City. The research data were obtained through traffic surveys conducted for seven consecutive days, from January 12 to January 18, 2026, during morning, midday, and evening peak hours. The side friction variables analyzed consisted of pedestrian movements (PED), parked or stopped vehicles on the roadway (PSV), and vehicles entering and exiting roadside access points (EEV). Road performance was evaluated based on traffic volume, road capacity, degree of saturation, level of service, and free-flow speed in accordance with the Indonesian Highway Capacity Guidelines (PKJI) 2023. Multiple linear regression analysis was performed using IBM SPSS software to determine the relationship between side friction and road performance. The results showed that the highest degree of saturation was 0.96 on the Talang Banjar direction with Level of Service (LOS) E, while the lowest degree of saturation was 0.49 on the Selincah direction with LOS A. Partial analysis indicated that on-street parking activities had the most significant effect on road performance, while simultaneously all side friction variables significantly influenced the degree of saturation. The coefficient of determination values of 0.900 for the Talang Banjar direction and 0.879 for the Selincah direction indicate that side friction activities have a very strong influence on the performance of Jalan Orang Kayo Pingai, Jambi City